Influência do regime de cheias na reprodução de espécies de peixes com diferentes estratégias reprodutivas da planície de inundação do rio Cuiabá, Alto Pantanal, Brasil. - Bailly, Dayani (2006)
The present study evaluated the influence of the flooding regime of the Cuiabá River on the reproductive dynamics of some fish species, with distinct reproductive strategies. This study aims to subsidize management actions in regulated rivers, especially towards biotic diversity in floodable areas. Samplings were carried out in 10 sites located in different areas of the basin, between March/2000 and April/2004. The reproductive strategies evaluated were long distance migrant, short distance migrant, sedentary with parental care and sedentary with internal fertilization. Period, duration and intensity of floods were the flooding attributes considered. Duration and time of spawning of fishes were evaluated using the index of reproductive activity (IRA) and inferences concerning the reproductive investment were based on residual analysis obtained by linear regressions between the gonadal weight and total weight. A close relationship between the reproductive dynamics and the flooding regime was observed, and the reproductive peaks of the four strategies always preceded flooding peaks. Intense floods favored gonadal development of long distance migrant species and species with parental care, but were less important for those with internal fertilization. In relation to juvenile survival, the occurrence of intense floods seemed crucial for strategies as long distance migrant, sedentary with parental care and internal fertilization, since such floods increased fish survival in the period of initial development. Differently, short distance migrant species seemed to be less dependent on floods for reproduction. These results indicate that excepting short distance migrant, the floods have a relevant role in the recruitment of species belonging to other reproductive strategies, influencing the spawning success as well as juvenile survival.